Tick Populations and Molecular Analysis of Anaplasma Species in Ticks from the Republic of Korea - Min-Goo Seo; Haeseung Lee; Badriah Alkathiri; KyuSung Ahn; Seung-Hun Lee; SungShik Shin; Seulgi Bae; Kyoo-Tae Kim; Min Jang; Sang-Kwon Lee; Yun Sang Cho; Kyung-Yeon Eo; et al. (Microorganisms, 2023)
The present study was performed to survey the dominant tick populations and molecularly determine the pathogenic agents of anaplasmosis in ticks from Gyeongsang, Republic of Korea. A total of 3825 questing ticks were collected by the flagging method from 12 sites near animal farms in Gyeongsang from March to October 2021. A molecular genomic study was performed with ticks stored in 70% ethanol to detect Anaplasma genes by the previously described method. The monthly incidence of ticks varied by developmental stages, i.e., nymphs, adults, and larvae, and each of their populations peaked in May, March, and October, respectively. The predominant tick species were Haemaphysalis longicornis, Haemaphysalis sp., Haemaphysalis flava, Ixodes nipponensis, and Amblyomma testudinarium in order. To determine the Anaplasma infection rate, collected ticks were pooled into 395 groups. The minimum infection rate (MIR) of Anaplasma was 0.7% (27 pools). That of A. phagocytophilum was highest (23 pools, MIR 0.6%), followed by A. phagocytophilum-like Anaplasma spp. clade B (2 pools, MIR 0.1%), A. bovis (1 pool, MIR 0.1%), and A. capra (1 pool, MIR 0.1%), respectively. In this study, five species of ticks, including unidentified Haemaphysalis species, were collected in 12 survey sites in Gyeongsang, but their prevalence was somewhat different according to the tick species and survey sites. Further, the incidence rate (6.8%) of 4 Anaplasma spp. was not as high in tick pools. However, the results of this study may offer a basis for future epidemiological research and risk assessment of tick-borne diseases.